Liposomal Nanocarriers and Herbal Therapeutics in the Management of Melanoma: A Comprehensive Review - Ankit Sharma; Priyanshu Saini; Sahil Yadav; Vikash; Poonam Arora; Kavita Attri (The Bioscan, 2026)
Melanoma remains one of the most biologically restless forms of skin cancer. It accounts for a smaller proportion of cutaneous malignancies than basal cell carcinoma or squamous cell carcinoma, yet it causes a disproportionate share of skin cancer mortality because it invades early, adapts quickly, and often survives therapeutic pressure. Immune checkpoint inhibitors, BRAF and MEK inhibitors, and refined surgical management have changed the outlook for many patients, but the field is still living with a hard problem: durable response is not guaranteed, toxicity can be serious, and resistance is common. In that unsettled space, liposomal nanocarriers and plant derived therapeutics have become more than a fashionable research topic. They offer a way to rethink how poorly soluble, chemically fragile, and pleiotropic natural molecules might be delivered to melanoma cells, immune cells, and the skin itself. This review examines liposomal nanocarriers for herbal and phytochemical agents in melanoma management, with attention to curcumin, quercetin, resveratrol, epigallocatechin gallate, berberine, apigenin, silymarin, silibinin, luteolin, and related compounds. The discussion covers melanoma biology, the rationale for lipid vesicular delivery, formulation design, topical and systemic routes, mechanistic pathways, combination therapy, safety, translational barriers, and future research priorities. A central argument runs through the review: liposomes can make herbal therapeutics more drug like, but they cannot rescue weak biology or poorly controlled experiments. The most convincing future work will therefore need stronger melanoma models, rational dose selection, pharmacokinetic evidence, immunological readouts, and manufacturing realism.